VD_FINDINFO Décision / 2016 / 149 vom 29. Februar 2016 - VD Tribunal cantonal (2016)
FRAIS DE LA PROCÉDURE, CLASSEMENT DE LA PROCÉDURE, PLAIGNANT, MORT, PRÉVENU | 319 al. 1 CPP (CH), 427 al. 2 CPP (CH), 429 CPP (CH), 432 CPP (CH)